Optimalisasi Digital Native di Era Industri 4.0 - Dewanti, Paula (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
Generation transformation be inline with the evolution and technological revolution that also contributes to a change in various fields. Digital generation, with their characteristic of be connected 24 hours per day, is comfortable with technology and prefers to communicate using technology services, rather than through conventional ways. Based on that, this generation can easily make an adjustments in the Industrial Age 4.0 where information availability is accessible fast and precise with the support of Information Technology. Located in one of Bali's well-established universities located in the center of tourism destinations of Jimbaran Bali, this study is applied to their newly accepted student candidate. Practically, the university itself has a proven E-Learning system in place. Given the opportunity to expand their English, before being officially registered on that system, these new learner, have no media to engage with their lecturers or classmates. Therefore, there is a need for educational technology that offers communication platforms, collaboration, and training. Applying descriptive analysis method, this research data is done with pre, post and evaluation scheme which is combination of conventional class learning, E-Learning, including obtaining a survey at the end of course, to get feedback from learners.Keywords-Blended learning, digital learning, native digital, industrial revolution, generation characteristic.